Harnessing Stevia rebaudiana for Zinc Oxide Nanoparticle Green Synthesis: A Sustainable Solution to Combat Multidrug-Resistant Bacterial Pathogens - Mohamed Tharwat Elabbasy; Rasha M. El Bayomi; Esraa A. Abdelkarim; Abd El-Salam E. Hafez; Mohamed S. Othman; Mohamed E. Ghoniem; Mai A. Samak; Muteb H. Alshammari; Fahad Awwadh Almarshadi; Tamer Elsamahy; Mohamed A. Hussein (Nanomaterials)
The rise of multidrug-resistant (MDR) bacteria in food products poses a significant threat to public health, necessitating innovative and sustainable antimicrobial solutions. This study investigates the green synthesis of zinc oxide nanoparticles (ZnO-NPs) using Stevia rebaudiana extracts to evaluate their antibacterial and antibiofilm activities against MDR Staphylococcus aureus strains isolated from sold fish samples. The obtained results show that the contamination with S. aureus reached 54.2% in the tested fish samples (n = 120), underscoring the urgent need for effective interventions. ZnO-NPs were successfully synthesized and characterized using UV-visible spectroscopy, FT-IR, XRD, and TEM, confirming their formation with an average size of 15.7 nm and reflecting their suitability for antimicrobial and biological applications. ZnO-NPs exhibited potent antibacterial activity, with a maximum inhibition zone of 24.4 ± 0.4 mm at 20 μg/disk, MIC values of 6.25–25 μg/mL, and MBC values of 12.5–50 μg/mL. Additionally, biofilm formation was inhibited by up to 92.1% at 250 μg/mL. Our mechanistic study confirmed that ZnO-NPs damage bacterial membranes and DNA, leading to the intracellular leakage of cell components that lead to bacterial cell lysis. The use of S. rebaudiana in ZnO-NP synthesis aligns with green chemistry principles, offering an eco-friendly alternative to conventional antibiotics and enhancing the bioactivity of ZnO-NPs, and may address the growing issue of antimicrobial resistance, thereby contributing to improved food safety and public health protection.